2017
DOI: 10.1371/journal.pone.0172100
|View full text |Cite
|
Sign up to set email alerts
|

Sr-substituted bone cements direct mesenchymal stem cells, osteoblasts and osteoclasts fate

Abstract: Strontium-substituted apatitic bone cements enriched with sodium alginate were developed as a potential modulator of bone cells fate. The biological impact of the bone cement were investigated in vitro through the study of the effect of the nanostructured apatitic composition and the doping of strontium on mesenchymal stem cells, pre-osteoblasts and osteoclasts behaviours. Up to 14 days of culture the bone cells viability, proliferation, morphology and gene expression profiles were evaluated. The results showe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
22
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(26 citation statements)
references
References 53 publications
1
22
0
1
Order By: Relevance
“…on strontium‐enriched biomaterials for bone regeneration concludes based on in vivo experiments that strontium is “an apparently safe and effective doping material for stimulating bone formation and remodeling” (Neves, Linhares, Costa, Ribeiro, & Barbosa, ). In vitro stimulation of proliferation and osteogenic differentiation of human bone marrow‐derived mesenchymal stem cells (Montesi, Panseri, Dapporto, Tampieri, & Sprio, ; Schumacher, Lode, Helth, & Gelinsky, ), and an inhibitory effect on osteoclasts activity in vitro (Montesi et al., ) were reported for strontium(II)‐modified calcium phosphate bone cements as well.…”
Section: Introductionmentioning
confidence: 91%
“…on strontium‐enriched biomaterials for bone regeneration concludes based on in vivo experiments that strontium is “an apparently safe and effective doping material for stimulating bone formation and remodeling” (Neves, Linhares, Costa, Ribeiro, & Barbosa, ). In vitro stimulation of proliferation and osteogenic differentiation of human bone marrow‐derived mesenchymal stem cells (Montesi, Panseri, Dapporto, Tampieri, & Sprio, ; Schumacher, Lode, Helth, & Gelinsky, ), and an inhibitory effect on osteoclasts activity in vitro (Montesi et al., ) were reported for strontium(II)‐modified calcium phosphate bone cements as well.…”
Section: Introductionmentioning
confidence: 91%
“…Recently, novel injectable, self-setting Sr-HA bone cements were prepared by mixing Sr-substituted α-TCP phases as unique inorganic precursors with disodium phosphate solutions enriched with alginate. In vitro tests showed that different concentrations of Sr 2+ were able to promote an inductive effect on mesenchymal stem cell differentiation, especially at 2 mol% concentration, and on pre-osteoblast proliferation and an inhibitory effect on osteoclasts activity [64]. Moreover, the addition of alginate significantly improved both injectability and cohesion, leading also to significantly higher compression strength when compared with alginatefree cements, without affecting the hardening process and with the absence of cytotoxic effects.…”
Section: Injectable Self-hardening Bone Cements With Biomimetic Compomentioning
confidence: 99%
“…On the other hand, a Sr loaded bone cement (Sr-BC) was prepared in different concentrations Sr/(Ca + Sr) = 0%, 2%, 5% in a different study where the experiment was only carried out in vitro on the mouse monocyte cell line (RAW 264.7) and the MC3T3-E1 cell line. 60 Further, a cement precursor was found composed of 58 wt% a-tricalcium phosphate, 24 wt% calcium hydrogen phosphate, 8.5 wt% hydroxyapatite and 8.5 wt% strontium carbonate and later mixed with a 4% aqueous disodium hydrogen phosphate solution to assist new bone formation in Sprague-Dawley rats, 61 and silicon (Si) and Zn doped brushite cements (BrCs) alone and in combination with insulin like growth factor 1 (IGF-1), coming to four different scaffolds: (IGF-1) BrC, (IGF-1) Si-BrC, (IGF-1) Zn-BrC, and (IGF-1) Si/Zn-BrC cements, on New Zealand white rabbits. 62 Moreover, scaffolds from very different compositions were found: SrO doped biosilicate scaffolds, fabricated by mixing Mg 2 SiO 4 and CaSiO 3 and adding SrO in different ratios, being 0SrO (0 wt%), 0.5SrO (0.5 wt%), 1SrO (1 wt%), 2SrO (2 wt%), and 3SrO (3 wt%), were used to treat MG-63 cells; 63 a zinc silicate mineral coated PLLA scaffold compared to a non-coated scaffold and tissue culture plastic (TCPS), cultured with adipocyte derived stem cells (ADSCs); 64 a strontium chloride (SrCl 2 ) coated porcine femur cancellous bone derived scaffold (CPB) subsequently coated with polycaprolactone (PCL) obtaining CPB/Sr/ PCL on hMSCs; 65 a sol-gel method synthesized hybrid scaffold incorporating: phosphate ions, calcium from calcium dichloride (CaCl 2 Á2H 2 O) and Sr from strontium dichloride hexahydrate (SrCl 2 Á6H 2 O) was incorporated into human osteoblast cell line (HOB) cultures; 66 a Sr folate (SrFO) loaded bio-hybrid porous scaffold obtained by interpenetrating beta tricalcium phosphate (bTCP) and polyethylene glycol dimethacrylate networks in contrast with a bTCP scaffold, which was used in an experiment in human dental pulp stem cells (HDPSCs) as well as in vivo in Wistar rats; 67 Wharton's jelly-derived mesenchymal stem cells (WJCs) were treated with either a rod-like nano hydroxyapatite (RN-HA) or a flake-like micro hydroxyapatite (FM-HA) as a coating for a Mg-Zn-Ca alloy scaffold in another study; 68 a Collagen type-I (Col-I) coated magnesium-zirconia (Mg-Zr) alloy, containing different quantities of Sr, where the scaffolds were divided into 3 samples: No-Sr, Low-Sr (1.82 wt%) and High-Sr (4.8 wt%) and later implanted into New Zealand white rabbits; 69 another Sr containing HA/polylactide composite group with four scaffolds was obtained: CT (control, Sr0/polylactide), SrL (Sr0.5/polylactide), SrM (Sr5/polylactide) and SrH (Sr50/polylactide), which were as well implanted into New Zealand white rabbits; 70 and lastly, three different studies chose to use a calcium silicate based bio-ceramic that contains Sr and Zn ions: strontium-hardystonite-gahnite (Sr-HT-gahnite) scaffolds, [71][72][73] since it has been recently studied due to its biocompatibility and exclusive microstructure (Fig.…”
Section: Tissue Engineering Based On Zn and Sr Containing Scaffoldsmentioning
confidence: 99%